The Study on Sugarcane Bagasse Fibres as Partial Aggregate Replacement in Lightweight Concrete Brick - Noh, Hamidun Mohd; Yarahim, Norakma Huda; Idris, Nur’ain (Research in Management of Technology and Business, 2020)
Bricks have been playing a significant role in building and construction for thousands of years. Nowadays, conventional bricks are produced from clay by using a high temperature of kiln firing and at the same time it releases large quantity of greenhouse gases. The excessive used of aggregates in brick mixture could make it rapidly diminished and effecting our construction industry in the future and besides, the waste management of agriculture or natural fiber such as sugarcane bagasse fiber are poorly handled. In this study, research was conducted on the performance of sugarcane bagasse fiber as partial aggregate replacement in lightweight concrete brick. The objectives of this research were to identifying optimum percentage for partial aggregate replacement using sugarcane bagasse fiber, to compare the strength of sugarcane bagasse fiber bricks with standard concrete brick and to observe the acceptance of sugarcane bagasse fiber as replacement material in concrete brick among the brick manufacturer. Qualitative method such as interview session was also applied in order to achieve the third objective of this research. There were two respondents involved which is one was from the brick manufacturer and the other one was a researcher in Johor area. There were four brick specimens casted for several proportions of 0%, 0.5%, 1% and 1.5% sugarcane bagasse fiber as partial aggregate replacement. Then, the compressive strength was conducted to determine the strength of the brick specimens. The finding shows that 0.5% of sugarcane bagasse fiber was the highest percentage of optimum strength with 2.5MPa than the others. From the qualitative analysis, both respondents agreed that this research required a lot more of improvement in order to increase the strength of the sugarcane bagasse fiber brick. This study would reduce the amount of sugarcane bagasse fiber disposed on the land for dumping purpose and could act as alternative material to lightweight concrete brick that have high standard and quality that can be proposed to the stakeholders.